Dimensions of Islamic Parenting Style for Children's Age in Parents Working in Urban Areas - Raras Syafrianty; Abu Mansur; Iredho Fani Reza (Indonesian Journal of Behavioral Studies, 2021)
This study aims to find out how the description of Islamic parenting for parents who work in urban areas. This study uses descriptive qualitative research methods. The technique used is perposive sampling technique, the research subjects are 6 married couples who have children aged 7-14 years, married couples who work and are aged 25-40 years. The data collection method used is semi-structured interviews. The results of this study indicate that Islamic parenting for parents who work in urban areas is that the subject applies discipline, strict supervision, limits, must follow orders and punish if children make mistakes and violate the rules that have been made.